Peningkatan Ketrampilan Berbicara Anak Usia Dini Melalui Kegiatan Bermain Peran (Penelitian Tindakan Kelas Pada Kelompok B Paud Anak Sholeh Purwokerto) - Mulyana, Ilva Dwi (STAIT Yogyakarta, 2018)
This study aims to improve speaking skills in early childhood earlychildhood Children Sholeh Purwokerto. This research is a class act who adaptedfrom Suharsimi Arikunto. The study consisted of two cycles and each cycleconsisted of three meetings. Data collection techniques gained throughobservation, documentation, interviews. Subjects in this study were children ingroup B ECD Children Sholeh Purwkerto the 16 children with details of nineboys and seven girls. Data analysis was performed by descriptive analytic. Thesuccess of the student is determined criteria ≥75%, it means the student issuccessful if achieving ≥ 75% of goals or values that should be achieved, lessthan the otherwise poorly managed. The results showed that the learningoutcomes of students' speaking skills through activities that play an increasingrole. Before speaking skill attainment measures the percentage of only 61.01%.In the first cycle speaking skills increased to 63.19%, thus the percentageincrease between prior action and the first cycle was 2.18%. In the second cycleincreased speaking skills become 88.48%. An increasing percentage of speakingskills early in the first cycle and the second cycle is equal to 25.29%.